Pharmacological stimulation and inhibition of insulin secretion in mouse islets lacking ATP-sensitive K(+) channels - Szollosi, A (Blackwell Publishing Ltd, 2010)
BACKGROUND AND PURPOSE: ATP-sensitive potassium channels (K(ATP) channels) in beta cells are a major target for insulinotropic drugs. Here, we studied the effects of selected stimulatory and inhibitory pharmacological agents in islets lacking K(ATP) channels. EXPERIMENTAL APPROACH: We compared insulin secretion (IS) and cytosolic calcium ([Ca(2+)](c)) changes in islets isolated from control mice and mice lacking sulphonylurea receptor1 (SUR1), and thus K(ATP) channels in their beta cells (Sur1KO). KEY RESULTS: While similarly increasing [Ca(2+)](c) and IS in controls, agents binding to site A (tolbutamide) or site B (meglitinide) of SUR1 were ineffective in Sur1KO islets. Of two non-selective blockers of potassium channels, quinine was inactive, whereas tetraethylammonium was more active in Sur1KO compared with control islets. Phentolamine, efaroxan and alinidine, three imidazolines binding to K(IR)6.2 (pore of K(ATP) channels), stimulated control islets, but only phentolamine retained weaker stimulatory effects on [Ca(2+)](c) and IS in Sur1KO islets. Neither K(ATP) channel opener (diazoxide, pinacidil) inhibited Sur1KO islets. Calcium channel blockers (nimodipine, verapamil) or diphenylhydantoin decreased [Ca(2+)](c) and IS in both types of islets, verapamil and diphenylhydantoin being more efficient in Sur1KO islets. Activation of α(2)-adrenoceptors or dopamine receptors strongly inhibited IS while partially (clonidine > dopamine) lowering [Ca(2+)](c) (control > Sur1KO islets). CONCLUSIONS AND IMPLICATIONS: Those drugs retaining effects on IS in islets lacking K(ATP) channels, also affected [Ca(2+)](c), indicating actions on other ionic channels. The greater effects of some inhibitors in Sur1KO than in control islets might be relevant to medical treatment of congenital hyperinsulinism caused by inactivating mutations of K(ATP) channels.